Neolithic and Bronze Age studies in Europe : from material culture to territories : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France), volume 13, session I-4 - Besse, Marie; Giligny, François (UISPP proceedings series, 2021)
Eight papers consider the neolithisation of the Iberian Peninsula; faunal exploitation in early Neolithic Italy; the economic and symbolic role of animals in eastern Germany; Copper Age human remains in central Italy; territories and schematic art in the Iberian Neolithic; and finally Bronze age hoards at a European scale.